Cestodiasis: A Narrative Review of Neglected Zoonotic Cestodes from Wild Rodents - Seli Nurmayani; Lucia Tri Suwanti; Mufasirin (Universitas Airlangga, 2026)
Zoonotic cestodes associated with wild rodents constitute an underrecognized component of neglected zoonotic diseases, particularly in resource-limited settings where ecological and sanitary conditions facilitate transmission. Although several rodent-borne cestodes, including Hymenolepis nana, Hymenolepis diminuta, Raillietina spp., and Inermicapsifer madagascariensis, are known to infect humans, their epidemiological significance remains insufficiently understood. This review synthesizes current evidence on the morphology, life cycles, host associations, clinical manifestations, and diagnostic challenges of zoonotic cestodes linked to wild rodents, with emphasis on their public health relevance. Available studies indicate that these infections are globally distributed but frequently underdiagnosed and underreported. Their predominantly asymptomatic nature, coupled with nonspecific clinical presentations and diagnostic limitations, contributes substantially to their neglected status. Children appear disproportionately affected, likely due to behavioral and hygiene-related factors that increase exposure risk. Rodents serve as important reservoirs, with numerous investigations documenting zoonotic cestode infections in peri-domestic and urban rodent populations. However, significant knowledge gaps persist regarding species diversity, geographical distribution, and transmission dynamics between rodents and humans. From a public health perspective, the overlooked nature of rodent-associated cestode infections highlights the need for improved surveillance, strengthened diagnostic capacity, and greater clinical awareness. Preventive strategies should prioritize sanitation, food safety, and health education, particularly in vulnerable populations. Addressing these gaps is essential for enhancing understanding of the epidemiology of zoonotic cestodes and for developing effective control and prevention measures.